Study on Effects of External Water Amount on Organic Intercalation of Montmorillonite and Its Mechanism - Limei Wu; Yongbin Wang; Lu Yang; Qing Wang; Changwei Xu (Advances in Materials Science and Engineering)
As an important clay mineral, montmorillonite (MMT) plays a pivotal role in various fields. Water has significant effects on the organification process of MMT, which is associated with the adsorption of organic matter onto MMT with different water contents. In this study, the influence of external water content on the organic intercalation of MMT and its mechanism are discussed from both experimental and simulation results. These results reveal that as the external water content increases, the interlayer spacing of organic MMT increases first and then decreases, while the degree of organification becomes increasingly stronger. Although the interlayer spacing of the organic MMT is the largest when the external water amount is relatively small (e.g., 10%), the molecular arrangement is disorderly and uneven, resulting in a low degree of organification. Increasing the external water content results in a more regular molecular arrangement, more compact intermolecular agglomerates, and a higher degree of order. Therefore, the addition of water plays a crucial role in the organification process of MMT, and the appropriate manufacturing technology should be selected according to the application field. The results of this study provide theoretical support for the preparation of organic MMT and also offer insight into the mechanism of organic intercalation.